2018
DOI: 10.3233/jad-170828
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine, IL-1β, Regulates Glial Glutamate Transporter via microRNA-181a in vitro

Abstract: Glutamate overload triggers synaptic and neuronal loss that potentially contributes to neurodegenerative diseases including Alzheimer's disease (AD). Glutamate clearance and regulation at synaptic clefts is primarily mediated by glial glutamate transporter 1 (GLT-1). We determined that inflammatory cytokines significantly upregulated GLT-1 through microRNA-181a-mediated post-transcriptional modifications. Unveiling the key underlying mechanisms modulating GLT-1 helps better understand its physiological and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…TNF-α can also increase the post-synaptic membrane ( Beattie et al., 2002 ). Both TNF-α and IL-1β increase intracellular and extracellular glutamate levels ( Ye et al., 2013 ; Zumkehr et al., 2018 ). TNF-α and IL-1β can also increase the glial glutamate transporter 1 which can facilitate glutamatergic transmission.…”
Section: Il-1β and Tnf-α Effects On Glutamate And Gamma-aminobutyric ...mentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α can also increase the post-synaptic membrane ( Beattie et al., 2002 ). Both TNF-α and IL-1β increase intracellular and extracellular glutamate levels ( Ye et al., 2013 ; Zumkehr et al., 2018 ). TNF-α and IL-1β can also increase the glial glutamate transporter 1 which can facilitate glutamatergic transmission.…”
Section: Il-1β and Tnf-α Effects On Glutamate And Gamma-aminobutyric ...mentioning
confidence: 99%
“…TNF-α and IL-1β can also increase the glial glutamate transporter 1 which can facilitate glutamatergic transmission. ( Ye et al., 2013 ; Zumkehr et al., 2018 ) IL-1β also modulates AMPA receptor expression and phosphorylation in neurons ( Lai et al., 2006 ). Nevertheless, multiple mechanisms are likely involved of how cytokines alter molecules that can alter sleep and interact with circadian biology and indicative of the necessity of sleep.…”
Section: Il-1β and Tnf-α Effects On Glutamate And Gamma-aminobutyric ...mentioning
confidence: 99%
“…Indeed, the spatially‐limited transient increase of cytokines such as IL‐1β induces the expression of glial glutamate transporter 1 (GLT1) as an important neurotransmitter transporter protein during physiological conditions. Therefore, this study suggested that IL‐1β can inhibit miR‐181a and thus, up‐regulate its target gene, GLT1 (Zumkehr et al, 2018). Another study showed a lower expression of miR‐186 in AD rat brains associated with higher levels of IL‐2 (D. M. Wu et al, 2018).…”
Section: The Interplay Between Ncrnas and Inflammation In Neurodegene...mentioning
confidence: 96%
“…Glial glutamate transporter 1 (GLT-1) contributes to the clearance and regulation of glutamate at synaptic clefts. An increase in miR-181a downregulated some synaptic proteins that are involved in plasticity in a 3xTg-AD mouse model and had a negative regulatory relationship with GLT-1, suggesting that miR-181a is a key mediator of the plasticity of glutamatergic synapses by controlling the expression of synaptic proteins, including GLT-1, in astrocytes (Zumkehr et al, 2015 , 2018 ).…”
Section: Involvement Of Mirnas In Astrocyte Dysfunction In Admentioning
confidence: 99%